PENGARUH MODEL PEMBELAJARAN TAKE AND GIVE TERHADAP HASIL BELAJAR SISWA TEMA VIII KELAS III SD RK BUDI LUHUR MEDAN - Jontono Samosir; Regina Sipayung; Reflina Sinaga; Darinda Sofia Tanjung (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This study aims to determine the effect of the Take and Give learning model on student learning outcomes with the PrajaMuda Karana theme in grade III SD RK Budi Luhur Medan. The research method used is an experimental method with quantitative research. To obtain the required data, data collection was used in the form of a test of 30 questions, a questionnaire of 17 statements, and documentation. The research at SD RK Budi Luhur Medan in class III was carried out from 17 to 18 May 2021. The number of samples was 30 students based on saturated sampling technique, based on the analysis, the pre test results were obtained with an average score of 68.73 in the sufficient category, the post test results with a score of 68.73. an average of 86.7 in very good category and the Take and Give learning model questionnaire with an average value of 63.3% in the high category. The results of the correlation analysis of the effect of the Take and Give learning model on student learning outcomes obtained a correlation value of rcount = 0.578 with rtable = 0.361. Thus, the value of rcount is greater than the value of rtable, so the correlation is very significant. Hypothesis testing with t-test obtained tcount = 3.268 with ttable = 1.697 at a significant level of 0.05. It can be concluded that there is an effect of the Take and Give learning model on student learning outcomes with the theme of PrajaMuda Karana for grade III SD RK Budi Luhur Medan Denai.Keywords: Take and Give Model, Learning Outcomes, Quantitative